MODEL PENGELOLAAN DIGITALISASI PENYIARAN DI INDONESIA - Ahmad Budiman (Jurnal Politica, 2015)
Broadcasting digitalization can increase efficiency of broadcasting infrastructure management which can result in maximum audio and audio visual broadcasting. Therefore, choice of models of broadcasting digitalization management cannot be separated from principles of efficiency and goals for attaining maximum digital dividend. Broadcasting digitalization moreover provides various opportunities for people to choose its dissemination technology and the ways its substances can be received. The essay says that broadcasting digitalization in Indonesia must be regulated in law regarding broadcasting.